Evaluation of phytosanitary products for the management of raspberry late leaf rust [Pucciniastrum americanum (Farl.) Arthur] - Delisle-Houde, Maxime; Demers, François; Tweddell, Russell (Phytoprotection, 2020)
Different phytosanitary products (Actinovate SP, Cabrio EG, Double Nickel 55, Fullback 125 SC, Kumulus DF, Nova, Phostrol, Pristine WG, Serenade Opti, Sirocco, StorOx) registered in Canada for the management of various diseases of horticultural crops but not for the management of late leaf rust (LLR) of raspberry were tested against the latter. Efficacy of each product was first determined in vitro on raspberry leaf discs. Based on in vitro efficacy, tested products can be ranked (from the most to the least effective) as follows: Nova, Sirocco, Fullback 125 SC, Pristine WG, Phostrol, Kumulus DF, StorOx, Cabrio EG, Serenade Opti, and Actinovate SP/Double Nickel 55. Five products (Fullback 125 SC, Kumulus DF, Nova, Phostrol, Sirocco) were further tested in the field. Foliar applications of Fullback 125 SC and Nova significantly reduced disease severity as compared with the control. This study shows that the triazole fungicides Fullback 125 SC and Nova were effective against LLR of raspberry as determined using in vitro and field assays and proposes a fast, inexpensive, and easy in vitro method to be used to select phytosanitary products to be tested for field assays.